PENGGUNAAN APLIKASI SURVEY HEART SEBAGAI MEDIA PENILAIAN HASIL BELAJAR SEJARAH PESERTA DIDIK DI SMA N 1 VII KOTO SUNGAI SARIK - Piya Wahyuni Junita; Aisiah Aisiah (Jurnal Kronologi, 2021)
This research is motivated by the implementation of the assessment of historical learning outcomes, there are still teachers using the conventional system in the form of paper and the process of assessing history learning outcomes when the teacher recaps the value of major errors when assessing test results, and the teacher's work takes a long time. The purpose of this study is to identify how practical it is to use the heart survey application in assessing student history learning outcomes and how effective the assessment of student history learning outcomes is in using the heart survey application at SMAN 1 VII Koto Sungai Sarik. This research method uses descriptive research type. The research subjects were 31 students and one compulsory history teacher. Data were collected through non-test using a questionnaire. The results showed that based on the teacher's response the level of practicality of using the heart survey application was classified as very practical (mean 3.90). And the practicality of using the heart survey application based on the responses of students is in the very practical category (mean 3.59). Then the effectiveness of the assessment of history learning outcomes based on the teacher's response shows the group is very effective (mean 3.73). Keywords: Effectiveness, Heart Survey Application, Assessment of Learning Outcomes